Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

today,I see a amazing math problem:

show that


This problem is from here.

But I consider sometimes,and I think it maybe use Taylor therom


Thank you,Now is 24:00 in beijing time,so I must go bed.I hope someone can help.Thank you

share|cite|improve this question
up vote 7 down vote accepted

The sum can be written as $$\sum_{n=0}^\infty \binom{4n}{n}\frac{1}{(3n+1)2^{4n+1}}=\frac{1}{2}{\;}_3F_2 \left(\frac{1}{4},\frac{1}{2},\frac{3}{4}; \frac{2}{3},\frac{4}{3};\frac{16}{27} \right)$$ For the Hypergeometric Function, see equation (25) of $${\;}_3F_2 \left(\frac{1}{4},\frac{1}{2},\frac{3}{4}; \frac{2}{3},\frac{4}{3};y \right) = \frac{1}{1-x^3}$$ where $x$ and $y$ are related by $$y=\left( \frac{4x(1-x^3)}{3}\sqrt[3]{4} \right)^3$$ Putting $y=16/27$, we get a polynomial equation in $x$. $$1=16 x^3(1-x^3)^3$$ According to Mathematica, this equation has only two real roots which are $$\begin{align*} \alpha &= \frac{1}{\sqrt[3]{2}} \\ \beta &= \left\{\frac{1}{6} \left(5-\frac{4}{\left(19-3 \sqrt{33}\right)^{1/3}}-\left(19-3 \sqrt{33}\right)^{1/3}\right) \right\}^{1/3} \end{align*}$$ Numericaly, $\beta$ gives the right answer. So, the final result is $$ \begin{align*}\sum_{n=0}^\infty \binom{4n}{n}\frac{1}{(3n+1)2^{4n+1}} &=\frac{1}{2\left(1-\beta^3 \right)} \\ &= \dfrac{\sqrt[3]{17+3\sqrt{33}}}{3}-\dfrac{2}{3\sqrt[3]{17+3\sqrt{33}}}-\dfrac{1}{3} \\ &\approx 0.543689\end{align*}$$

share|cite|improve this answer

The transformed series in Marin's post seems suspiciously like Taylor's expansion of Bring radical $$\begin{aligned}\sum_{n=1}^{\infty}\dfrac{\binom{4n-4}{n-1}}{2^{4n-3}(3n-2)} &= \sum_{n=0}^{\infty} \binom{4n}{n} \frac{1}{(3n + 1)2^{4n + 1}} \\ &= \frac{16^{1/3}}{2} \sum_{n=0}^{\infty} \binom{4n}{n} \frac{\left ( 16^{-1/3} \right )^{3n + 1}}{(3n + 1)} \\ &= \frac{1}{2^{1/3}}\sum_{n = 0}^{\infty} \frac{\left(16^{-1/3}\right)^n}{n!} \left [\frac{d^{n-1}}{dz^{n-1}} \left ( 1 + z \right )^{4n} \right ]_{z = 0}\end{aligned}$$

The last sum is the Lagrange-Burmann inversion formula applied to $\phi(z)=(1+z)^4$. It is straightforward now that the series (exlcuding the constant factor $1/2^{1/3}$) is one of the two real roots of the quartic $z^4 + z + 16^{-1/3}$. One can exclude $-1/2^{1/3}$ via invoking a numerical check, and thus

$$\sum_{n=1}^{\infty}\dfrac{\binom{4n-4}{n-1}}{2^{4n-3}(3n-2)} = \dfrac{\sqrt[3]{17+3\sqrt{33}}}{3}-\dfrac{2}{3\sqrt[3]{17+3\sqrt{33}}}-\dfrac{1}{3} \blacksquare$$

share|cite|improve this answer

Hint: the right side is a root of $27 z^3 + 18 z - 34$. There is a way to solve equations of the form $x^p + a x + b = 0$ using generalized hypergeometric functions.

share|cite|improve this answer

$\newcommand{\angles}[1]{\left\langle #1 \right\rangle}% \newcommand{\braces}[1]{\left\lbrace #1 \right\rbrace}% \newcommand{\bracks}[1]{\left\lbrack #1 \right\rbrack}% \newcommand{\dd}{{\rm d}}% \newcommand{\isdiv}{\,\left.\right\vert\,}% \newcommand{\ds}[1]{\displaystyle{#1}}% \newcommand{\equalby}[1]{{#1 \atop {= \atop \vphantom{\huge A}}}}% \newcommand{\expo}[1]{\,{\rm e}^{#1}\,}% \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,}% \newcommand{\ic}{{\rm i}}% \newcommand{\imp}{\Longrightarrow}% \newcommand{\pars}[1]{\left( #1 \right)}% \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}}% \newcommand{\sgn}{\,{\rm sgn}}% \newcommand{\ul}[1]{\underline{#1}}% \newcommand{\verts}[1]{\left\vert #1 \right\vert}% \newcommand{\yy}{\Longleftrightarrow}$

$\ds{% {\cal S} \equiv \sum_{n = 1}^{\infty}{{4n - 4 \choose n - 1} \over 2^{4n - 3}\,\pars{3n - 2}} = {1 \over 2} \sum_{n = 0}^{\infty}{4n \choose n}\,{\pars{1/16}^{n} \over 3n + 1} = {16^{1/3} \over 2} \sum_{n = 0}^{\infty}{4n \choose n}\,{\pars{16^{-1/3}}^{3n + 1} \over 3n + 1}}$.

$$ \mbox{Let's define}\quad {\rm f}\pars{z} \equiv \sum_{n = 0}^{\infty}{4n \choose n}\,{z^{3n + 1} \over 3n + 1} \quad\mbox{such that}\quad {\cal S} = {16^{1/3} \over 2}{\rm f}\pars{1 \over 16^{1/3}} $$

\begin{align} \!\!\!\!{\rm f}'\pars{z} &= \sum_{n = 0}^{\infty}z^{3n}{4n \choose n} = \sum_{n = 0}^{\infty}z^{3n}\int_{\verts{z'}\ =\ 1^{-}} {\pars{1 + z'}^{4n} \over z'^{n + 1}}\,{\dd z' \over 2\pi\ic} = \!\!\!\int_{\verts{z'}\ =\ 1^{-}}\!{\dd z' \over 2\pi\ic}\,{1 \over z'} \sum_{n = 0}^{\infty}\bracks{z^{3}\pars{1 + z'}^{4} \over z'}^{n} \\[3mm]&= \int_{\verts{z'}\ =\ 1^{-}}\!{\dd z' \over 2\pi\ic} {1 \over z' - z^{3}\pars{1 + z'}^{4}} \end{align}

With WA, we try to find the zeros of $ax^{4} - x + 1 = 0$ $\pars{~a \equiv z^{3}, \quad x \equiv z' + 1~}$ and they $\underline{\bf look}$ quite involved. The interesting value of $a$ is $a = z^{3} = 1/16$ and the behavior in $\pars{0,z_{m}}$ with $z_{m} > 16^{-1/3}$. With WA, we look for zeros of $x^{4} -16x + 16 = 0$. It $\underline{\bf yields}$ the following roots, in terms of $z'$: $$ z' = 1\,,\quad0.0874\,,\quad -2.5437 \pm 2.2303\,\ic $$ It's clear that there is one root close to zero but ${\bf \mbox{we don't know how the}\ z' = 1\ \mbox{root evolves when}\ z\ \mbox{moves away of}\ z = 16^{-1/3}}$. The contribution of the root $z_{0}$ "close to zero" is given by:

$$ \lim_{z' \to z_{0}}{z' - z_{0} \over z' - z^{3}\pars{1 + z'}^{4}} = {1 \over 1 - 4z^{3}\pars{1 + z_{0}}^{3}} = {1 \over 1 - 4z^{3}\pars{z_{0}/z^{3}}^{3/4}} = {1 \over 1 - 4z^{3/4}z_{0}^{3/4}} $$

Notice that $z_{0}$ is a function of $z$. We hope that a precise ( analytical ) solution of the zeros mentioned above will yields ${\rm f}\pars{z}$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.